Atuação de profissionais de enfermagem na área de fitoterapia: uma revisão integrativa de literatura - DIAS, Bianca Duarte Vitorio da Fonseca (2020)
The overall objective was to understand the importance of knowledge of nursing professionals about herbal medicine. Specifically, we sought to investigate public health in Brazil; highlight the role of nurses and good nursing practices and also investigate the importance of herbal knowledge in the treatment of some diseases. This is an integrative literature review (RIL) research, descriptive with qualitative approach, having as its source the Virtual Health Bank (BVA) platform, which pleases several sites related to human health, such as LILACs, Scielo, PUBMed. enabling a relevant research in academic, field or empirical works. The study verified the importance of knowledge on herbal medicine use among nurses and the importance of their role in their applicability to the assisted population. Ongoing training and capacity building is also needed, not only on their effectiveness, but on laws and programs approved by the Ministry of Health that include the use of herbal medicine in some cases, mainly to empower and enhance culture and knowledge. place. Therefore, it is relevant to use strategies that employ herbal medicine in the healthcare reality, especially in primary care, in order to ensure greater resolution of the local health system, while preserving the culture and popular practices of certain regions.